The impact of the COVID-19 pandemic on the use of urban green spaces by international youth in Bonn - Soer, Annebel (SLU/Dept. of Urban and Rural Development, 2021)
Throughout the COVID-19 pandemic in Germany, international youth is undergoing manifold negative impacts on their living situation, mobility, mental and physical health and their social life. It is well-known that urban green space (UGS) offers multiple benefits for all age groups, and there are specific advantages for youth in particular, which impact their lifestyle and usage of UGS during COVID-19. In this thesis, usage of urban green spaces in the city of Bonn are being studied, while the study focuses on international youth with specific lifestyle traits, which define their challenges and limitations while living in Bonn during COVID-19. This thesis researches the changes in usage of UGS by international youth during COVID-19, and will study the impacts of these changes on social cohesion, physical activity and mental wellbeing – three pillars derived from a study by Hartig et al. Additionally, the study will briefly highlight how these experiences can lead to more inclusive policy in relation to UGS.